PEMIKIRAN ISMAIL RAJI AL-FARUQI MENGENAI ISLAMISASI ILMU PENGETAHUAN - Mahsus Mahsus; Betty Adinda Wijaya (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2022)
The figure of Al-Faruqi is a productive person, all of his writings contain bright ideas and theories to maintain the integration of science which is packaged in the big frame of the Islamization of science. The idea of Islamization is a science that emerged as an answer to the opposition between theological fields and the insights that were collaborated from modern scientific disciplines and Islamic culture. The development of science has such a great effect in the world of education. However, there is a negative impact from the development of this modern science overriding the values in the teachings of Islam. The Islamization of knowledge itself is a necessity that cannot be replaced by Muslim scientists. Likewise the goals and principles of Islamization